Analysis Of The Influence Of Motivation And Perceptions Of Organizational Support On Teacher Performance Based On The Implementation Of The Four Pillars Of Unesco Education - Yuli Rusniati; Budi Prijanto (Al-Makki Publisher, 2024)
This study aims to analyze the influence of work motivation and perceived organizational support on the performance of civil servant teachers of public high schools in Bogor City, using the implementation of the Four Pillars of UNESCO Education as a performance measurement variable. The data collection method was carried out through a questionnaire distributed to 120 respondents of public high school civil servant teachers in Bogor City. Data analysis was conducted using multiple linear regression techniques. The results showed that work motivation has a significant positive effect on teacher performance, and perceived organizational support also has a significant positive effect on teacher performance. In addition, the results of the analysis show that work motivation and perceived organizational support simultaneously affect teacher performance as measured by the implementation of the four pillars of UNESCO Education. These findings are expected to add to the theoretical scientific repertoire and have important implications for education management and school leadership in improving the performance of civil servant teachers of public high schools in Bogor City.